Nutritional Value, Sugar Content, Acidity, Fiber Content, Total Bacteria, and Acceptability of Mixed Fruit Kefir and Milk Fruit Kefir - Wijaningsih, Wiwik; Wulandari, Desi; Sunarto, Sunarto (Jurnal Riset Kesehatan, 2025)
Kefir is a probiotic-rich functional beverage, and the addition of fruit enhances its nutritional composition, sensory characteristics, and consumer acceptability. This study analyzed twelve types of mixed fruit kefir and milk-based fruit kefir, focusing on nutritional value, sugar content, acidity, fiber levels, total bacterial count, and acceptability. The results showed that energy content ranged from 29.4 to 78.2 kcal per 100 grams, with mango kefir (50%) having the highest energy value. Protein content varied from 1.5% to 2.5%, with banana kefir (30%) containing the highest amount. Sugar content ranged from 1.6% to 12.6%, while acidity levels varied from 1.0% to 1.8%, influencing taste and microbial stability. Fiber content ranged from 1.2% to 3.4%, and total bacterial count varied between 26,666,667 and 2,247,000,000 CFU/g, confirming kefir’s probiotic potential.Sensory analysis revealed that mango kefir (50%) and pineapple kefir (50%) were the most preferred, while banana kefir (30%) had the lowest acceptability. These findings suggest that fruit-based kefir formulations can optimize both nutritional value and sensory appeal, positioning kefir as a highly nutritious and functional beverage.